ANALISIS PROGRAM NON DRAMA TERHADAP MINAT PROMOSI DAN MINAT MASYARAKAT BERKUNJUNG DALAM PERAN SERTA STASIUN TELEVISI - Jaqualine Pramanta Putra; Fauzi Syarief; Susana Susana (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2022)
Communities is important aspect in the survival of a tourist destinations and the community also an important aspect in the success a program a television show where in the program present information devoted to the communityAs for the kind of research used is research quantitative with the methods descriptive verifikatif which is to explain x, y and looking for relation of them in size sample as much as 140 respondents. The sampling techniques used is random sampling .Analysis techniques the data used analytics linear regression multiple. The research results show positive results and significant on variables subjects that is content program, format program, duration program and simultaneously to interest visit community. Magnitude impact of the Program of interest visit communities is a very important aspect for the continuity of tourism places in the program.